Snail trails a meta-analysis on induced resistance of plants and seaweeds to Gastropod Herbivores - Bustamante, Bless Cyra O.; CAdiz, Geofe O. (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Plants and seaweeds have evolved various adaptations against herbivory. One of these adaptations is chemical defense that can be triggered by different cues like the locomotion mucus of gastropods. Herbivore-induced defense is more commonly studied on insects while studies on the mucus of gastropod herbivores are limited. Thus, this study assessed through meta-analysis the extent to which gastropod mucus elicits a defensive response in plants and brown algae in terms of the production of anti-herbivore compounds, and investigated the different factors that may explain why defense responses vary among different plants and algae. A search was conducted on different databases and the data from qualified studies were then extracted and analyzed. In this study, 78 observations from 12 studies that tested for the effect of gastropod mucus on plants or seaweed were obtained. Plants and seaweed similarly showed a large increase in the concentration of herbivory-associated compounds when exposed to gastropod mucus, indicating that this is a general response in both groups. A subgroup analysis revealed that the extent to which plants and brown algae exhibit this defensive response is similar despite being distantly related organisms. However, several factors can affect this response, including the species of gastropod, the feeding behavior of the gastropod (i.e. whether it is a specialist or generalist), the species of algae, and the time elapsed after the herbivore attacked the plant (for the plant studies). This study demonstrates how both plants and brown algae defend themselves against gastropod herbivory which can threaten ecosystems.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. June 2022